종합검진 수검자의 관상동맥 전산화단층 혈관조영술 검사에서 관상동맥질환의 위험요인과 관련성 분석 - 최민경; Min-gyeong Choi; 곽종혁; Jong-hyeok Gwak; 김광; Gwang Kim; 이삼열; Sam-yol Lee (한국방사선학회 논문지, 2019)
본 연구는 건강검진 목적으로 시행된 관상동맥 CT에서의 성별, 연령에 따른 관상동맥질환 발견율에 대한 유용성과 글루코스, 총 콜레스테롤, 내장지방, 체질량지수, 중성지방, 고밀도지단백질(HDL), 저밀도지단백질(LDL) 각각의 인자들과 관상동맥질환과의 관련성에 대해 알아보았다. 총 299명의 수검자를 대상으로 후향적 분석을 실시 한 결과 관상동맥질환 발견율에 대해서는 남성, 50세 이상에서의　유병율이 높은 것으로 나타났으며, 통계적으로 유의성을 보였다. 특히　남성의　유병율(37.9％)은　여성의　유병율(17.0%)　보다　약 ２배가　높은 것으로　확인되었다. 또한　관상동맥질환과 관계되는 혈액학적　요인으로는 글루코스와 고밀도지단백질(HDL)이 통계적으로 유의성을 보였다. 관상동맥질환의 예방 및 관리를 위해서는 글루코스와 고밀도지단백질(HDL)의 조절이 필요할 것으로 보이며, 다른 혈액학적 인자들과는 통계적으로 유의성은 낮았지만, 관상동맥질환에 대한 관리의 필요성이 확인되었다. 주요　결과로서　선별검사 목적으로 관상동맥 CT의 사용은 방사선 피폭 등의 문제점으로 인해 수검자의 성별, 나이를 고려하여 시행하는 것이　좋을　것으로　생각되며,　관상동맥 CT 시행　이전에　비침습적인　방법들의　선행검사를　통한　관상동맥　질환　검사가　필요함을　제안한다. The purpose of this study is to evaluate the usefulness of coronary computed tomography angiography of coronary artery disease for the purpose fo health screening according to gender and age. In addition the association between hematological factors (Glucose, total cholesterol, visceral fat, body mass index, triglycerides, high density lipoprotein (HDL), low density lipoprotein (LDL)) and coronary artery disease is investigated. A retrospective analysis of coronary computed tomography angiography with 299 subjects showed that the detection rate of coronary artery disease was higher in men over 50 years of age and it was statistically significant. In particular, the prevalence rate of men (37.9%) was about 2 times higher than that of women (17.0%). Glucose and HDL as hematological factors associated with coronary artery disease were statistically significant. The prevention and management of coronary artery disease seems to require the control of glucose and high density lipoprotein (HDL). Although it is not statistically significant with other hematological factors, the need for management of coronary artery disease was identified. the coronary computed tomography angiography of coronary artery has higher radiation doses than other CT scans. Therefore, for the purpose of screening, coronary computed tomography angiography should be considered in consideration of the sex and age of the examinee, and detection of coronary artery disease through other non-invasive tests should be prioritized over coronary computed tomography angiography.